Drifting with Direction: Going astray in Jean Genet. (3rd October 2018) - Brueton, Joanne
Abstract : This article offers a double-focused reading of the drift in Jean Genet's work and its reverberations in the dérive of the Situationist International. Tracking Genet's biographical nomadism through the Mediterranean to the Middle East, I explore how he performs Deleuze and Guattari's notions of deterritorialisation by displacing the fixed positions and affiliations by which any identification is made possible. He becomes the literal embodiment of Giacometti's Homme qui marche 1 (1960): an artist forever caught in the interstice between walking away and walking towards. Yet this personal drift also has a radically political echo: in his tribute to deviance and deviants, replete with their etymological proximity to the dériviste, Genet strays away from the straight, upstanding backbone of normative politics. Instead, his texts experiment with a practice of obliqueness that demands that we see past the inauthenticity of an overly accessible culture of image and hypervisibility to locate meaning in the off-centre and the unseen. Despite the SI's excoriation of theatre, I contend that Genet's theorisations of a 'theatre-cemetery' revolutionise the dérive not as a performance, but as a transversal space of radical detachment: a double heterotopia that escapes urban geographies of total domination and forward-marching narratives of material progress by putting death and absence centre stage.